Safe Enough? A Building Code to Protect Our Cities and Our Lives. Issue 2 (May 2016) - Porter, Keith A.
Seminal works on earthquake engineering hold that greater seismic resistance of building stock is impractical; that the public is unwilling to pay for it; that the public has no proper role in setting code philosophy; and that current seismic provisions encode the proper performance goals. Recent projects undermine these conventionalities. In light of performance expectations for new buildings, the code seems to almost guarantee that a future large but not very rare earthquake will damage enough buildings to displace millions of people and hundreds of thousands of businesses from a major metropolitan area, producing a catastrophe more severe than Hurricane Katrina. A discussion with the public should take place in which we reconsider how to measure risk and how to balance risk and construction cost in code objectives.